Manifestation of paroxysmal nocturnal hemoglobinuria as repeated acute kidney injury - Manish R Balwani; Vivek B Kute; Pankaj R Shah; Maulin Shah; Umesh Varyani; Hargovind L. Trivedi (Society of Diabetic Nephropathy Prevention, 2016)
The triad of hemolytic anemia, pancytopenia, and thrombosis makes paroxysmal nocturnal hemoglobinuria (PNH) a truly unique clinical syndrome. Intravascular hemolysis in PNH can lead to a severe hemolytic episode with massive hemoglobinuria which can cause acute kidney injury (AKI) probably from acute tubular necrosis (ATN). A 15 -year-old girl was admitted with history of fever, diarrhea, vomiting followed by decreased urine output since 3 days. Urinalysis showed nil protein, no red blood cells (RBCs) on microscopy. Plasma hemoglobin level, total leukocyte count, platelet count, and serum creatinine were 6.5 gm/dl, 6440/μl, 205 000/μl, and 3.1 mg/dl, respectively. She received 3 units of packed red blood cells and the patient was discharged with normal renal function test with a diagnosis of acute gastroenteritis with recovered AKI. After 8 months she again had fever, vomiting, nausea with decreased urine output since 3 days. Laboratory investigations showed hemoglobin - 5.5 gm/dl, total leukocyte count - 1550/ μl, platelet count - 165000/μl, and serum creatinine - 4.89 mg/dl. Serum LDH level was 2188 U/l. She was managed conservatively with steroids, antibiotics and she recovered her kidney functions to normal in a week. Presentation of repeated AKI with hemolytic anemia in a short span after fever led us to perform flow cytometric analysis of peripheral blood granulocytes which revealed the presence of PNH clone. PNH may present with renal disease and anemia only even without classical history of hematuria or venous thrombosis. Thus it needs high index of suspicion as early diagnosis and treatment will help in preventing repeated episodes of AKI and thus chronic kidney disease.